Comparative effect of olmesartan and candesartan on lipid metabolism and renal function in patients with hypertension: a retrospective observational study - Nakayama Tomohiro; Takahashi Yasuo; Nishida Yayoi; Soma Masayoshi; Asai Satoshi (Cardiovascular Diabetology, 2011)
Abstract Background Angiotensin II receptor blockers (ARBs), including olmesartan and candesartan, are widely used antihypertensive agents. Many clinical studies have demonstrated that ARBs have organ-protecting effects, e.g., cardioprotection, vasculoprotection and renoprotection. However, the effect of prolonged olmesartan monotherapy on lipid metabolism in patients with hypertension is less well studied. We performed a retrospective observational study to compare the effects of olmesartan with those of candesartan, focusing on lipid metabolism and renal function. Methods We used data from the Clinical Data Warehouse of Nihon University School of Medicine obtained between Nov 1, 2004 and Feb 28, 2011, to identify cohorts of new olmesartan users (n = 168) and candesartan users (n = 266). We used propensity-score weighting to adjust for differences in all covariates (age, sex, comorbid diseases, previous drugs) between olmesartan and candesartan users, and compared serum chemical data including serum triglyceride (TG), LDL-cholesterol (LDL-C), total cholesterol (TC), potassium, creatinine and urea nitrogen. The mean exposure of olmesartan and candesartan users was 126.1 and 122.8 days, respectively. Results After adjustment, there were no statistically significant differences in all covariates between olmesartan and candesartan users. The mean age was 60.7 and 61.0 years, and 33.4% and 33.7% of olmesartan and candesartan users were women, respectively. There were no statistically significant differences in mean values for all laboratory tests between baseline and during the exposure period in both olmesartan and candesartan users. In olmesartan users, the reduction of serum TG level was significant in comparison with that in candesartan users. Other parameters of lipid profile and renal function showed no statistically significant difference in the change from baseline to during the exposure period between olmesartan and candesartan users. Conclusions In this study, we observed a more beneficial effect on lipid metabolism, a reduction of serum TG, with olmesartan monotherapy than with candesartan monotherapy. However, there were no clinically significant changes in the levels of all test parameters between baseline and during the exposure period with both drugs. These results suggest that the influence of olmesartan or candesartan monotherapy on lipid metabolism and renal function is small, and that they can be safely used in patients with hypertension.